The politics of policing between force and legitimacy - Deflem, Mathieu (Bingley, U.K. : Emerald, 2016)
This volume in the series Sociology of crime, law, and deviance edited by Mathieu Deflem addresses contemporary issues of policing with a focus on the characteristics of police power as a coercive force in society and its continued need for legitimacy in a democratic social order. The book brings scholars together to discuss a variety of important topics concerning police and policing. Developments and problems associated with police power are at the very front of current public debate. In the broader constellation of the culture of modern crime control, police institutions enjoy a privileged status. Continued developments in technology and surveillance have affected policing as have continued and new crime problems. Not least of all, of course, the legitimacy of policing has recently been questioned because of several highly-publicized incidents involving police violence. The chapters in this book provide clarification on these and related aspects of police and policing in society. This collection is valuable for students and scholars in sociology, criminology, law, political science, and public policy.
Fair policing from the inside out / Maarten Van Craen -- Enhancing police legitimacy by promoting safety culture / Jordan C. Pickering, David A. Klinger -- Policing through third parties : increasing coercion or improving legitimacy? / Janet Ransley -- Three pillars of police legitimacy : procedural justice, use of force, and occupational culture / William Terrill, Eugene A. Paoline III, Jacinta M. Gau -- Conservatives and the constabulary in Great Britain : cross-dressing conundrums / Robert Reiner -- Investigations on the legitimacy of the Swiss police : actual debates and empirical evidence / Silvia Staubli -- Politicization and legitimacy of police in India / Arvind Verma -- Explaining police attitudes toward the use of force : the case of Buenos Aires / Nicole E. Haas -- Improving police legitimacy by measuring all that matters : reflections from the United States and France / Jack R. Greene ... [et al.] -- Mental illness, race, and policing / Melissa Thompson ... [et al.] -- Police shootings in black and white : exploring newspaper coverage of officer-involved shootings / Charles F. Klahm IV, Jordan Papp, Laura Rubino -- Paradise lost : white flight and the construction of a criminogenic origin myth / Aaron Roussell, Jason Dunbar -- Citizen journalism and police legitimacy : does recording the police make a difference? / Ashley K. Farmer, Ivan Y. Sun -- Watching the watchers : theorizing cops, cameras, and police legitimacy in the 21st century / Kirk Miller -- The politics of private policing : no force and no legitimacy? / Massimiliano Mulone -- The triangle of recruitment, selection, and training in 21st century policing / Maria Haberfeld.
Print version record
Keywords: Social Science -- Criminology; Police procedures; Police -- Political aspects; Police ethics; Police misconduct